Spectroscopy of Lanthanide Doped Oxide Materials - Dhoble, Sanjay J.; Pawade, Vijay B.; Swart, Hendrik C.; Chopra, Vibha (Oxford : Woodhead Publishing, 2020)
Spectroscopy of Lanthanide Doped Oxide Materials provides a comprehensive overview on the most essential characterization techniques of these materials, along with their key applications. The book describes the application of optical spectroscopy of lanthanides doped inorganic phosphor hosts and gives information about their structure and morphology, binding energies, energy of transition and band gap. Also discussed are the properties and applications of rare earth doped inorganic materials and the barriers and potential solutions to enable the commercial realization of phosphors in important applications. The book reviews key information for those entering the field of phosphor research, along with the fundamental knowledge of the properties of transition series elements under UV/Visible/NIR light exposer. Low-cost materials methods to synthesize the materials and spectroscopic characterization methods are also detailed.
Includes bibliographical references and index.
Keywords: Rare earth metals -- Spectra; Spectrum analysis; Phosphors -- Spectra; Light emitting diodes; 0; Light emitting diodes; Phosphors -- Spectra; Rare earth metals -- Spectra; Spectrum analysis